Quality of Life of Chronic Renal Failure Patients Undergoing Hemodialysis Therapy - Endrat Kartiko Utomo; Totok Wahyudi (Proceeding of International Conference on Science, Health, And Technology, 2022)
Background: Changes in lifestyle associated with the complex treatment of hemodialysis, which ultimately affects the mental or psychological and social of the patient. Changes in physical, psychological functioning, lack of mobility, work problems, unemployment in activities, fatigue and fear of future challenges are problems faced by people with chronic renal failure undergoing hemodialysis therapy. Objective: To determine the quality of life in chronic renal failure patients undergoing hemodialysis therapy. Method: Type of descriptive research using Analytical Survey with a total sample of 53 respondents taken with purposive sampling techniques and quality of life instruments measured with KDQOL-SF 3.6. Results: Average quality of life symptom/problem list 66.90, effect kidney disease 65.68, burden kidney disease 50.47, SF-12 Physical Health 40.69, and SF-12 Mental Health 50.20. Conclusion: The role of families and hospitals is able to improve and maintain the quality of life of chronic renal failure patients undergoing hemodialysis therapy.